A Tracer Study of the Graduates of Education Graduate Programs 2018-2022 of the University of Negros Occidental- Recoletos Graduate School - Gentova, Cecile S.; Madrigal, Dennis V.; Bual, Joel M. (Technium Social Sciences Journal, 2023)
This explanatory sequential inquiry determined the contribution of graduate education to the development of skills, the satisfaction with the delivery of the graduate school program and services, and the practice of graduate attributes of the graduates of education graduate programs of the University of Negros Occidental-Recoletos Graduate School. Likewise, it explored deeper insights on the quantitative data to generate a broader perspective on the graduates’ experiences on the contributions of the graduate school to the development of their skills, satisfaction with the delivery of programs and services, and graduate attribute practice. The participants were the graduates of education graduate programs during 2018-2022 and determined using purposive sampling. In data gathering, survey questionnaire and semi-structured in-depth interview were employed. In analyzing the data, mean and standard deviation were utilized in the quantitative analysis while Lichtman’s (2013) 3C’s were used in the qualitative data. The data revealed a very great extent of the contribution of graduate studies, extremely satisfied with the delivery, and a very great extent of graduate attribute practice. Meanwhile, the qualitative data presented salient findings. The graduate education experiences provide the development of their competencies, knowledge, skills, and attributes, which leads to better opportunities in their profession. Also, their satisfaction develops their attributes of humility, Christian values, integrity, love, and the quest for excellence, thus forming values essential to the practice of profession and life in general. Moreover, this study validated that tracer studies could assist the graduate school in complying with the accreditation and quality assurance measure requirements for a quality management system. Furthermore, the satisfaction of graduates encourages continual improvement towards engaging the alumni in open, mutually beneficial ways and spreading knowledge to uplift others and positively use their influence to impact the community, the country, and the world.